Evaluating the Influence of Photo Order on Park Visitors' Perceptions of Crowding at Buffalo National River. (4th July 2022) - Cribbs, Tyler W.; Sharp, Ryan L.; Brownlee, Mathew T. J.
Abstract: Visual-based methods are common in visitor use management research because they often support empirical evaluations of structural norms, particularly related to crowding in parks and other protected areas. Consequently, researchers and managers continue to investigate method bias and improve visual-based approaches and tools. This study continues this improvement process by assessing whether the order of photographs viewed by park visitors in a field setting influences their norms and thresholds related to crowding. To accomplish this, a study was conducted at Buffalo National River, Arkansas, using sequential and nonsequential photograph presentation order. Results indicate that photograph presentation order had limited to no effect on park visitors' normative thresholds and associated norms – a finding both supported by and incongruent with previous photo order studies. As a result, this research contributes to the growing body of work in the study of research methods for protected area and visitor use management.